Fixed drug eruption due to acetaminophen. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
Fixed drug eruption is a disease that has a definite cause often identified with the history, with oral provocation tests or according to some Authors with patch tests (1); however, its pathogenesis is not clear. The cause is always a drug, although sometimes foods seem to play a causal role; however, in some of these cases the foods were contaminated with drugs (2). The most frequently involved drugs are non-steroidal anti-inflammatory drugs, sulfonamides and barbiturates. However, with changing therapeutic habits we noticed that the ability to cause fixed drug eruption was not the same for different drugs. In Italy up to 20 years ago the most widely used anti-inflammatory drug was feprazone; it was frequently responsible for fixed drug eruption in children; when feprazone was replaced by acetaminophen fixed drug eruption got exceptional in children.